Association between social jet lag, quality of diet and obesity by diurnal preference in Finnish adult population. (4th May 2021) - Suikki, Tiina; Maukonen, Mirkka; Partonen, Timo; Jousilahti, Pekka; Kanerva, Noora; Männistö, Satu
ABSTRACT: The evening type has been associated with unhealthy behaviors and adverse health outcomes, such as unhealthy dietary habits and obesity. Misalignment between biological and social rhythms, referred to as social jet lag (SJL), has been considered to explain these outcomes, because evening types are more prone to SJL. However, the existing evidence has been inconsistent and SJL by diurnal preference has hardly been examined. We examined the associations between SJL, the quality of the diet, and the prevalence of obesity by diurnal preference. This dataset included 6779 Finns (55% women, aged 25–74 years) from the National FINRISK 2012 and DILGOM 2014 studies. Diurnal preference was assessed with a shortened version of the Morningness-Eveningness Questionnaire (MEQ). SJL was calculated with the sleep-corrected formula (SJLsc ). SJL was divided into three groups by the degree of SJL (<1h, ≥1h but <2h and ≥2h). The dietary intake was assessed with a validated food frequency questionnaire (FFQ) and the quality of the diet with the Baltic Sea Diet Score. Body weight, height, and waist circumference (WC) were measured, and the body mass index (BMI) was calculated (kg/m 2 ). Analysis of covariance (ANCOVA) followed by Bonferroni multiple comparison post-hoc tests and logistic regression models were used to analyze the differences between the lowest and the highest SJL groups by diurnal preference. In the highest SJL group (≥2h), there were more evening types than morning types (7%-points, p < .001). Overall, those in the highest SJLsc group were on average younger than those in the lowest SJLsc group ( p < .001). Also, those in the highest SJLsc group tended to have lower adherence to the Baltic Sea Diet compared to the participants in the lowest SJLsc group, but this difference reached significance only in morning types ( p = .006). Furthermore, morning types in the highest SJLsc group had higher BMI and WC compared to the morning types in the lowest SJLsc group (BMI, p = .016; WC, p = .012). In conclusion, evening types had on average more SJL than morning types, but the degree of SJL was associated with the quality of the diet and obesity only in the morning types.